HUBUNGAN SELF DIRECTED LEARNING READINESS DENGAN PRESTASI MAHASISWA SEMESTER III FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH - Resti Rahmadika Akbar; Cyntia Puspa Dewi; Meta Zulyati Oktora; Mutiara Anissa (Yayasan Nusantara Hasana Berdikari, 2025)
Background: One of the most influencing factors in achieving a satisfying score in an academic record is from the student himself. It is in form of the readiness for them to learn independently. This situation is often called sdlr. It is the level of readiness or the ability to learn independently. The important role for the sdlr formation in oneself can be used to score the level of students success in achieving their academic records. Objective: The aim of this study to know the correlation between self-directed learning readiness and 3rd-semester students Medical Faculty of Baiturrahmah University’s achievement. Methods: This study was conducted in the third semester of Medical Faculty of Baiturrahmah University from March to September 2020. This study belongs to unpaired comparative analytic by using Cross-Sectional Study design. The population of the study is all of the third-semester students of Baiturrahmah University with 105 samples. The sample is taken randomly. The union varied data analysis shown in frequency distributed table and bivariate analysis uses a Kruskal-Wallis test with SPSS program. Results: There is correlation between self directed learning readiness with students score in the third-semester students of medical faculty of baiturrahmah university, it is obtained the result of p=0,001 shows the most sldr score is in the high level, acquired by 67 students (63.8%) and the most concern is from the very satisfying grade acquired by the students, 78 students (74,3%). So it can be assumed that there is a significant relationship between sldr and the students' academic achievement. Conclusions: There is a significant correlation between Self Directed Learning Readiness and the third semester of Medical Faculty of Baiturrahmah University academic achievement.